Monitoring of Pantograph-Catenary Interaction by using Particle Swarm Based Contact Wire Tracking - Aydin, Ilhan; Karakose, Mehmet; Akin, Erhan (Ieee, 2014)
With the increasing of the train speeds in railway transport, the safety and early detection of any anomaly becomes an important issue. This paper analyzes the contact point between pantograph and catenary by using particle swarm based tracking. The position of contact wire is tracked along all frames. The obtained tracked signal is analyzed by S-transform and the pantograph condition is detected. The proposed method has been verified by using real pantograph-videos and good results has been obtained when the performance of the proposed tracking is compared to mean-shift algorithm.
21st International Conference on Systems, Signals and Image Processing (IWSSIP) -- MAY 12-15, 2014 -- Dubrovnik, CROATIA
Keywords: Object tracking; particle swarm optimization; railway transportation; pantograph-catenary system; condition monitoring